Implementasi Tele Psychological First Aid (PFA) pada Layanan Konseling - Zahratika Zalafi (Assertive: Islamic Counseling Journal, 2022)
Psychological First Aid (PFA) or Initial Psychological Assistance assists individuals experiencing pressure or abnormal conditions such as trauma and disasters to feel calm and cope better with their situation. The Covid-19 pandemic is the latest crisis that underlies the importance of organizing PFA because the psychological impact it causes increases anxiety in the community. This study aims to reveal the application of PFA to telePFA in Counseling Services to deal with changing patterns in people's lives when the co-19 pandemic hit. The research was conducted in a qualitative descriptive manner. Research data was collected through the observation method of modules and the application of telePFA to the counseling service of Friends of Sehati UIN Prof. K.H. Saifuddin Zuhri Purwokerto. Data collected and analyzed accompanied by triangulation. The study results show that through the six steps of look, listen, comfort, link, protect and hope, the telePFA service of Teman Sehati UIN Prof. K.H. Saifuddin Zuhri Purwokerto helps clients overcome anxiety, frustration, and even post-traumatic depression or in abnormal mental health conditions